1992
DOI: 10.1007/bf00685548
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of doxorubicin-induced myocardial and haematological toxicities in rats by the iron chelator desferrioxamine

Abstract: Biochemical and histopathological evaluations of the protective effects of the iron-chelator desferrioxamine against the cardiac and haematological toxicities of doxorubicin in normal rats were carried out. A single dose of doxorubicin (15 mg/kg, i.v.) caused myocardial damage that manifested biochemically as an elevation of serum cardiac enzyme [glutamic oxaloacetic transaminase (GOT), lactic dehydrogenase (LDH) and creatine phosphokinase (CPK)] and cardiac isoenzyme levels and histopathologically as a swelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Similar results were obtained in rats treated with gasoline vapors [19], in rats treated with Nigerian Bonny light crude oil [1,2], in rats treated with cypermethrin [20] and in rats treated with Doxorubicin [21]. It was found that treating rats with crude oil was associated with anemia of the haemolytic type [18,22].…”
Section: Discussionsupporting
confidence: 55%
“…Similar results were obtained in rats treated with gasoline vapors [19], in rats treated with Nigerian Bonny light crude oil [1,2], in rats treated with cypermethrin [20] and in rats treated with Doxorubicin [21]. It was found that treating rats with crude oil was associated with anemia of the haemolytic type [18,22].…”
Section: Discussionsupporting
confidence: 55%
“…Thus, our findings indicate that the presence of SOD at the appropriate cellular location is critical for the detoxification of ADR-induced tissue injury. It has been shown that some antioxidants or compounds with antioxidant properties could suppress ADRinduced myocardial injury in rodents (2,4,(35)(36)(37). However, these results did not clearly indicate the subcellular site where the antioxidants protected the cardiac tissue from ADR toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratories, Al-Harbi et al [9] and Osman et al [10] have reported that the iron chelator desferrioxamine can protect the heart and blood elements of normal rats and mice against the toxicity induced by doxoru bicin. They explained and documented that desferrioxamine could inhibit lipid peroxida tion and prevents the liberation of harmful free radicals which may be the cause of such damage.…”
Section: Discussionmentioning
confidence: 99%
“…It shows a broad spectrum of antitumor activities in ani mal tumor systems [1,2] and in certain hu man cancers [3,4], The optimal use of cispla tin is prevented by a dose-limiting nephrotox icity [5], The exact mechanism of this nephro toxicity is not yet known. However, lipid per oxidation or free radicals generated by cispla tin have been suggested to be responsible for the nephrotoxicity [6,7], The liberation of free radicals can be completely inhibited by the iron chelator desferrioxamine [8], Al-Harbi et al [9] and Osman et al [10] have reported that desferrioxamine can protect against doxorubicin-induced cardiac and he matological damage in normal rats and mice via inhibition of lipid peroxidation. There fore, the aim of the present study was to inves tigate the effect of desferrioxamine pretreat ment on cisplatin-induced lipid peroxidation and nephrotoxicity in normal rats.…”
Section: Introductionmentioning
confidence: 99%